Simultaneous wastewater treatment and electricity generation using microbial fuel cell (MFC) - Shamalah A/P Sree Moorthy (School of Environmental Engineering, University Malaysia Perlis, 2012)
In current developing state of world, MFC is becoming a growing technology in producing sustainable energy and its application in wastewater treatment system units is completely a new form of approach. Applying MFC to treat wastewaters and its simultaneous energy production also has its own economic benefits as cost of wastewater treatment could be reduced. Generally, MFC will use microorganisms to convert substances into electricity allowing it to be able to treat wastewaters and producing alternative source of energy. However, research is still being done on MFCs feasibility as the electricity generated by MFC cannot be directly used as it has low voltage and current output. In this paper, a lab scale MFC was developed using synthetic wastewater and it was operated under different conditions. Design of an MFC was done to identify and obtain maximum current output and COD removal that was generated by the MFC system. A maximum current output of 247.9A was obtained and a maximum of 620mV open circuit voltage was recorded by the MFC system analyzed. MFC system designed was also capable of obtaining a COD removal efficiency of 70.9%.